PENGARUH ARUS KAS OPERASI, FIRM SIZE, DAN MOMENTUM TERHADAP RETURN SAHAM PADA PERUSAHAAN YANG TERDAFTAR DALAM INDEKS LQ 45 PERIODE 2014 – 2018 DI BURSA EFEK INDONESIA - TITO MARTA SUGEMA DASUKI (JURNAL AKUNTANSI DAN SISTEM INFORMASI, 2020)
The purpose of this study was to determine the effect of cash flows from operating activities, firm size (Firm Size) and momentum on stock returns. The variables of this study consist of cash flow from operating activities, firm size (Firm Size) in proxies with total assets, momentum and stock return. The research method used is descriptive and verifikatif analysis. The population in this study are companies listed in the LQ 45 index period 2014-2018. While the sample in this study is determined by purposive sampling method so that obtained 16 sample companies. The analytical method used in this research is multiple linear regression analysis method which is done with the help of computer program SPSS version 21.0 for windows, in the use of multiple regression model of research data must be free from the possible deviations of classical assumptions, namely normality test, multicolinearity test, test of autocorrelation and heteroscedasticity test, besides the coefficient of determination analysis is used to describe the ability of independent variable in explaining the dependent variable, while the t-test and F-statistic test are used to test the effect of the independent variables on the dependent variable partially and simultaneously. The results of this study show that partially cash flow from operating activities, and firm size (Firm Size) in proxikan with total assets do not affect the stock return. While momentum has a significant effect on stock return. Simultaneously show that cash flow from operational activity, firm size (Firm Size) and momentum have significant effect to stock return.